2000
DOI: 10.1152/ajpheart.2000.279.6.h2807
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II enhances β-adrenergic receptor-mediated vasorelaxation in aortas from young but not old rats

Abstract: beta-Adrenergic receptor (beta-AR)-mediated (cAMP-dependent) vasorelaxation declines with advancing age. It has been shown that angiotensin II (ANG II), a potent vasoconstrictor, enhances cAMP-mediated vasorelaxation. Therefore, we questioned whether ANG II could reverse age-related, impaired beta-AR-mediated vasorelaxation and cAMP production. Pretreatment of aortic rings from 6-wk-old or 6-mo-old male Fischer 344 rats with ANG II significantly enhanced vasorelaxation induced by isoproterenol (Iso), a beta-AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Since the AT-receptors are well known to be rapidly down-regulated [ 1 , 20 ], cessation of [Ca 2+ ] i increase may be due to the down-regulation of AT-receptors. We also found that the angiotensin II-induced contraction was completely inhibited by the AT 1 receptor antagonists, 1 µ M losartan [ 7 ] or 10 nM KRH-594 [ 28 ], supporting the results by Schutzer et al [ 27 ] in rat aortic tissue and by Castoldi et al . [ 6 ] in cultured rat aortic smooth muscle cells.…”
Section: Discussionsupporting
confidence: 90%
“…Since the AT-receptors are well known to be rapidly down-regulated [ 1 , 20 ], cessation of [Ca 2+ ] i increase may be due to the down-regulation of AT-receptors. We also found that the angiotensin II-induced contraction was completely inhibited by the AT 1 receptor antagonists, 1 µ M losartan [ 7 ] or 10 nM KRH-594 [ 28 ], supporting the results by Schutzer et al [ 27 ] in rat aortic tissue and by Castoldi et al . [ 6 ] in cultured rat aortic smooth muscle cells.…”
Section: Discussionsupporting
confidence: 90%
“…Also, in aortic rings from Fischer 344 rats, Ang II significantly enhances vasorelaxation induced by isoproterenol and enhances isoproterenol-induced cAMP production. 28 In contrast, in other model systems, Ang II either inhibits cAMP production or has no effect on cAMP production. For example, in human fetal mesangial cells, Ang II attenuates isoproterenol-induced cAMP production.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, changes in physiology could be due to age-related changes in the processing and degradation of cAMP through phosphodiesterases. We have determined that there are no age-related changes in general phosphodiesterase inhibitor-mediated vasorelaxation using 3-isobutyl-1-methylxanthine (IBMX), a nonspecific phosphodiesterase subtype inhibitory agent [ 62 ]. However, others [ 63 ] found that using a low dose of IBMX caused impaired cAMP accumulation in blood vessel preparation from older rats.…”
Section: Age-related Changes In Vascular Functionmentioning
confidence: 99%
“…In terms of vasorelaxation being affected was a study that found that angiotensin II can enhance cAMP-mediated vasorelaxation via angiotensin II-type 1-receptors (AT 1 ) [ 96 ]. We examined the interaction among aging, β -AR-mediated vasorelaxation, and angiotensin II [ 62 ]. Our results showed that this effect of angiotensin II on agonist-mediated vasorelaxation was limited to young (6-week-old) or adult (6-month-old) rats, was absent in aged (12- and 24-month-old) animals, and was mediated by angiotensin II-type 1 receptors.…”
Section: Age-related Changes In Vascular Functionmentioning
confidence: 99%